CoPc and CoPcF16 on gold: Site-specific charge-transfer processes - Petraki, Fotini; Peisert, Heiko; Uihlein, Johannes; Aygül, Umut; Chassé, Thomas (Beilstein Journal of Nanotechnology, 2014)
Interface properties of cobalt(II) phthalocyanine (CoPc) and cobalt(II) hexadecafluoro-phthalocyanine (CoPcF16) to gold are investigated by photo-excited electron spectroscopies (X-ray photoemission spectroscopy (XPS), ultraviolet photoemission spectroscopy (UPS) and X-ray excited Auger electron spectroscopy (XAES)). It is shown that a bidirectional charge transfer determines the interface energetics for CoPc and CoPcF16 on Au. Combined XPS and XAES measurements allow for the separation of chemical shifts based on different local charges at the considered atom caused by polarization effects. This facilitates a detailed discussion of energetic shifts of core level spectra. The data allow the discussion of site-specific charge-transfer processes.
Keywords: Auger parameter; charge transfer; interfaces; organic semiconductors; photoemission; phthalocyanines; polarization screening